Kebudayaan Tionghoa Dalam Ritual Agama Buddha - Iqbal Fernandez; Jonathan Martin (Jurnal Budi Pekerti Agama Buddha, 2023)
Linked to religion, religious youth, in this case Buddhist youth in Temanggung Regency, seem to be trying to actualize the urge to organize into the experience of religious values ​​and humility. This organization was founded on April 10 2016. They call themselves the Temanggung-Kendal-Semarang Buddhist Youth. The Buddhist youth of Temanggung is an inseparable part of the younger generation in Indonesia in general. The younger generation is currently developing themselves as well as a potential resource for progress for the nation and state which is embodied by motivation, morality and spiritual religious values.